Redefining Loyalty: A Qualitative Exploration of the Job-Hopping Paradox and Occupational Commitment in Generation Z - -, Stefanie Aurelia; Kuncoro Dewi Rahmawati (Universitas Islam Indonesia, 2026)
Job hopping among Generation Z is frequently stigmatized as a crisis of organizational loyalty. However, traditional metrics that equate commitment with tenure fail to reflect the shifting values of the modern workforce. This qualitative study explores how Indonesian Gen Z employees navigate the tension between frequent career mobility and organizational commitment. Through in-depth interviews (N=6) with active job hoppers, thematic analysis reveals a critical paradox: while participants frequently exit organizations, they maintain robust occupational commitment, remaining steadfast in their professional fields. Our findings indicate that job hopping is not a rejection of responsibility but a strategic response to toxic leadership, excessive workloads, and career stagnation. For Gen Z, loyalty has transitioned from